Herb-in vitro cyp interaction of Cytochrome P1A2 on Malaysian traditional herbs / Nur Amirah Mohd Noor Azami - Mohd Noor Azami, Nur Amirah (Faculty of Pharmacy, 2010)
Many people believe that traditional medicine can be use as alternative to treat many diseases and some of them take both medicines at same time. They do not notice that there have risks of interactions between herbs and drug leading to toxicity or loss of therapeutic efficacy. The purpose of this study is to evaluate the interactions of Malaysian traditional herbs with CYP1A2 enzymes. CYP1A2 is one of the major member of CYP and it constitute about 12-20% of the total CYP content and it mostly a hepatic enzymes. Vivid®CYP450 Screening Kit had been use to study the inhibition activity of Malaysian traditional herbs. α-naphthoflavone is use as positive control that showed 100% inhibition and solvents control which is DMSO showed 0% inhibition or no inhibition. Result showed 27 herb which are Biji kedaung, Bunga mukmin, Cabai pintal, Getah katira, Halba, Kadukai besar, Kadukai kecil, Kacip Fatimah, Kayu angin, Kayu lilit, Ketumbar, Kulit kayu manis, Lada pahit, Lebai samad, Lengkuas, Manjalawi, Mas cotek, Pakawali, Pegaga, Pinang, Pulau waras sari, Selasih, Sembaranthu, Senduduk, Serai wangi, Tenggek burung and Tering pipit show inhibitions at concentration 0.1mg/ml. From 56 Malaysian traditional herbs species, there are 27 herbs shown inhibition on concentration 1 mg/ml which is Kulit kayu manis, Pulau waras sari, Sembaranthu and Senduduk. Other herbs do not show any significant inhibition. Keywords: CYP1A2, Malaysian traditional herb, inhibition